2009
DOI: 10.1007/s10067-009-1188-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies and kidney involvement in patients with systemic sclerosis

Abstract: Antiphospholipid (aPL) antibodies are often detected in systemic autoimmune diseases. The aim of the study was to examine the correlation between the presence of aPL and certain markers of renal function in systemic sclerosis (SSc). Fifty patients (pts) with SSc were examined for the presence of antibodies to cardiolipin (aCL) and to anti-beta 2 glycoprotein I (a-B2GPI) in immunoglobulin M (IgM) and IgG class. Moreover, serum levels of creatinine, cystatin C, and glomerular filtration rate (GFR) were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
0
23
0
2
Order By: Relevance
“…Microangiopathy causes tissue hypoperfusion and ischemia, which lead to atrophy of the neural fibers and autonomic dysfunction. Muscarinic-3 acetylcholine receptor autoantibodies, detected in the majority of patients with GI involvement, may directly disrupt cholinergic neurotransmission in the smooth muscles [4]. As a consequence, esophageal reflexes are weakened or suppressed, greatly impairing peristalsis.…”
Section: Gastrointestinal Involvement In Systemic Sclerosismentioning
confidence: 99%
“…Microangiopathy causes tissue hypoperfusion and ischemia, which lead to atrophy of the neural fibers and autonomic dysfunction. Muscarinic-3 acetylcholine receptor autoantibodies, detected in the majority of patients with GI involvement, may directly disrupt cholinergic neurotransmission in the smooth muscles [4]. As a consequence, esophageal reflexes are weakened or suppressed, greatly impairing peristalsis.…”
Section: Gastrointestinal Involvement In Systemic Sclerosismentioning
confidence: 99%
“…Наибольший интерес представляет иссле-дование E. Wielosz и соавт. [76], в котором предпринята по-пытка выявить связь между наличием аФЛ у пациентов с ССД и почечной функцией. Все пациенты, страдающие ССД, как лимитированной, так и диффузной формой, бы-ли распределены в две группы в зависимости от выявления у них аФЛ в любых, даже слабо позитивных, титрах.…”
Section: нефропатия ассоциированная с антифосфолипидным синдромомunclassified
“…For symptomatic disorders of the esophagus, it was reported that 74% of SSc patients had some GERD symptoms [14], but only 50% of SSc patients with RE had typical GERD symptoms [15]. Some previous studies denoted that neither disease duration nor the type of SSc has any significant association with GERD symptoms [16,17].…”
Section: Introductionmentioning
confidence: 99%